(untitled) (SAARC Journal of Agriculture, 2018)
Relative abundance of leaf and plant hoppers species regarding plant growth stages and temperature were studied in the rice variety BINA10 field at the research farm of Patuakhali Science and Technology University (PSTU) during October 2013 to April 2014. The percent relative abundance of leafhoppers was in the rank order of M. dorsalis> C. brevis> N. virescens> N. malayanus> N. cincticeps> N. nigropictus at seedling, early and maximum tillering stages while N. virescens> C. brevis> M. dorsalis> N. nigropictus> N. malayanus> N. cincticeps at reproductive stage. The percent relative abundance of planthoppers was in the rank order of N. nervosa> N. lugens> S. furcifera at seedling and reproductive stages while N. lugens> N. nervosa> S. furcifera at early tillering and N. nervosa> S. furcifera and N. lugens at maximum tillering stages. The abundance of all leafhopper species showed highly negative relationship with temperature. This relationship can be expressed by 81% (R2=0.806) for N. virescens, 80% (R2= 0.801) for N. nigropictus, 65% (R2=0.653) for N. cincticeps, 60% (R2=0.600) for C. brevis and 70% (R2=0.698) for M. dorsalis. Among three planthopper species, population of S. furcifera showed highly negative relationship with temperature and this relationship can be expressed by 71% (R2=0.707). The abundance of N. nervosa showed poor positive relationship with temperature. This relationship can be expressed by 3 % for N. nervosa (R2=0.030). N. lugens showed poor negative relationship with temperature and this relationship can be expressed by 31% (R2=0.310) for N. lugens. SAARC J. Agri., 16(1): 95-104 (2018)